Planning of Communication Strategy for Islamic Religious Counselors in Carrying Out Their Main Tasks and Functions in North Labuhanbatu Regency - Awan, Uli Susanti Sri; Zainun, Zainun; Mailin, Mailin (Budapest International Research and Critics University, 2021)
This study aims to planning formulation strategy in accordance with the eight specialization fields that are ideally attached to the performance of extension services for non-civil servant extension workers. The eight specializations include reading and writing the Koran (BTA), halal products, radicalism and splinter sects, the sakinah family, HIV/AIDS & drugs, zakat, endowments, and religious harmony (KUB). The research method used is qualitative. The data sources for this research are literature studies, related documents, and interviews with Islamic Religious Counselors. The communication strategy of Islamic Religious Counselors in carrying out their main tasks and functions in North Labuhanbatu Regency is by planning that has been formulated in the extension work group meeting and in its implementation using a da'wah strategy using Islamic communication principles such as qaulan layyina, qaulan maisura, qaulan sadida, qaulan baliga. Implementation of activities or work programs carried out by Islamic religious instructors in the form of religious activities such as assemblies of taklim and other religious events that reflect community social care. Evaluation the last stage in this process involves the readiness of the assessment, implementation, and results of the implemented program based on evaluation feedback on how the program was successful or not. Evaluations are carried out by extension workers by making written reports on each activity.